Rose Red - Baxley, Craig R.; King, Stephen, 1947-; Travis, Nancy, 1961-; Keesler, Matt. (Marina del Rey, CA : Trimark Home Video, 2002)
Stephen King tells the ultimate haunted house story in Stephen King's Rose Red, a lavish four-hour extravaganza written by the horror novelist, originally aired as an ABC-TV miniseries. Borrowing its set-up from Shirley Jackson's novel The Haunting of Hill House, Rose Red tells the story of a psychology professor (Nancy Travis) who assembles a diverse group of extrasensory adepts to spend a weekend in a 90-year-old haunted house in hopes of bringing out its supernatural side.
English track: Dolby digital 5.1.
Spanish track: Dolby digital 5.1.
With: audio commentary; theatrical trailer; one hour behind-the-scenes featurette, Unlocking Rose Red, the diary of Ellen Rimbauer; interactive menus; scene selection; storyboards.
Nancy Travis, Matt Keesler, Kimberly J. Brown.
MPAA rating: PG-13.
DVDs.
Keywords: Haunted houses -- Drama; Horror films; Video recordings for the hearing impaired; Feature films